Factors Impacting Customer Attitude toward Buying Halal Cosmetics in Jabodetabek - Clarita, Ni Made Adelia; zimbalist, shannon baladewa; Setiowati, Rini (Journal the Winners: Economics, Business, Management, and Information System Journal, 2020)
The research aimed to analyze the relationship between religiosity, product involvement, customers’ knowledge toward customers’ attitudes on halal cosmetics, and the relationship between customers’ attitudes on halal cosmetics towards customers’ intention to buy them. The research used a self – administrated questionnaire with close-ended questions. The questionnaire was distributed as pretest to 30 respondents offline. Furthermore, the researchers received answers from 302 respondents out of 350 that were distributed. To assess the relationship between knowledge, involvement, and religiosity, a structural equation modeling technique was used. Data were analyzed using Smart PLS software to test validity and reliability. The findings its show that there is a positive relationship between knowledge, religiosity, and product involvement towards costumers’ attitudes of halal cosmetics on Indonesian Muslim women. Moreover, the results indicate that Muslim women in Indonesia have more positive attitudes and intentions towards halal cosmetic products. The results of the research give implications to the firm in competing for the general and international brands for the halal cosmetic industry.